2013
DOI: 10.1136/archdischild-2012-303470
|View full text |Cite
|
Sign up to set email alerts
|

Why collaborate with children in health research: an analysis of the risks and benefits of collaboration with children

Abstract: Involvement of service users in decision making, in both clinical and research settings, has become a central feature of many health and research funding policies in the last 15 years. Over the same timeframe, there has been an increasing focus on children's rights, promoted by the UN Convention of the Rights of the Child, which gives children a right to be involved in decisions that affect their lives. In a research setting, this has resulted in increased engagement of children in research, as opposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(73 citation statements)
references
References 33 publications
0
73
0
Order By: Relevance
“…The understanding that children and young people should be involved in decisions which affect them has been increasingly reflected in UK law, guidance, regulation and policy in relation to health and social care (Department of Health, 2013;Franklin and Sloper, 2005). But there has been less attention paid to the experiences and impact of involving children and young people than the involvement of adults (Bird et al, 2013). Involvement should lead to research, and ultimately services, that better reflect young people's priorities and concerns (Brady et al, 2012;Fleming and Boeck, 2012).…”
Section: Young People's Involvement In the Y-sbnt Studymentioning
confidence: 99%
“…The understanding that children and young people should be involved in decisions which affect them has been increasingly reflected in UK law, guidance, regulation and policy in relation to health and social care (Department of Health, 2013;Franklin and Sloper, 2005). But there has been less attention paid to the experiences and impact of involving children and young people than the involvement of adults (Bird et al, 2013). Involvement should lead to research, and ultimately services, that better reflect young people's priorities and concerns (Brady et al, 2012;Fleming and Boeck, 2012).…”
Section: Young People's Involvement In the Y-sbnt Studymentioning
confidence: 99%
“…As Bird et al (6) already concluded, reporting of participatory research with children must improve, for example by using the Guidance for Reporting Involvement of Patients and Public (GRIPP) checklist (30), in order to be able to assess successful and unsuccessful methodologies (4). When this has been done a few times for each participatory method, comparative studies into the differences and similarities and pros and cons can be executed properly.…”
Section: General Considerations For Using Participatory Methods In Pementioning
confidence: 99%
“…Seven narrative reviews of child involvement in social sciences and four reviews of child participation in medical research were identified; one of these reviews is a systematic review. The reviews are predominantly focused on necessity of participatory research (8), ethics (3,9,10), risks and benefits (6), and practicalities such as inclusion or dissent (2,9,11-13) ( Table 2). None of the reviews extensively described participatory methods for pediatric medical research.…”
Section: Search and Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations